Cobalt(ii)-catalyzed benzylic oxidations with potassium persulfate in TFA/TFAA. Issue 36 (4th July 2019) - Li, Tianlei; Li, Jishun; Zhu, Zihao; Pan, Weidong; Wu, Song
Abstract : A Co-catalyzed C(sp 3 )–H oxygenation reaction to furnish diverse aldehydes from methylarenes in TFA/TFAA is reported. This transformation demonstrated high chemo-selectivity, and tolerated with various methylarenes bearing electron-withdrawing substituents. Abstract : A cobalt-catalyzed C(sp 3 )–H oxygenation reaction to furnish aldehyde was herein reported. This transformation demonstrated high chemo-selectivity, and tolerated various methylarenes bearing electron-withdrawing substituents. This reaction provided rapid access to diverse aldehydes form methylarenes. Notably, TFA/TFAA was used for the first time as a mixed solvent in cobalt-catalyzed oxygenation of benzylic methylenes.